2021
DOI: 10.1177/09637214211013775
|View full text |Cite
|
Sign up to set email alerts
|

The Vicious Cycle Linking Stereotypes and Social Roles

Abstract: Members of social categories defined by attributes such as sex, race, and age occupy certain types of social roles much more than members of other social categories do. The qualities that define these roles become associated with the category as a whole, thus forming a stereotype. In a vicious cycle, this stereotype then hinders category members’ movement into roles with different demands because their stereotype portrays them as well matched to their existing roles but not to these new roles. This vicious cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 36 publications
1
65
0
1
Order By: Relevance
“…Students from lower SES backgrounds have on average lower performance in national exams, lower rates of progression to higher education (Department for Education, 2020), and are underrepresented in positions associated with educational attainment (Arulampalam et al, 2005;Jones, 2016). These sociocultural factors contribute to the stereotype that high academic achievers are from high SES backgrounds (Eagly & Koenig, 2021), and feed into those groups' social identities (Easterbrook et al, 2019;Manstead, Easterbrook, & Kuppens, 2020). Indeed, there is evidence that SES is associated strongly and positively with stereotypes of competence (Cuddy, Fiske, & Glick, 2007;Fiske, 2010), and that there are descriptive and prescriptive stereotypes that link lower SES with academic incompetence among adults and children (Batruch, Autin, & Butera, 2017;Croizet & Claire, 1998;Goudeau & Croizet, 2016).…”
Section: Identity Incompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Students from lower SES backgrounds have on average lower performance in national exams, lower rates of progression to higher education (Department for Education, 2020), and are underrepresented in positions associated with educational attainment (Arulampalam et al, 2005;Jones, 2016). These sociocultural factors contribute to the stereotype that high academic achievers are from high SES backgrounds (Eagly & Koenig, 2021), and feed into those groups' social identities (Easterbrook et al, 2019;Manstead, Easterbrook, & Kuppens, 2020). Indeed, there is evidence that SES is associated strongly and positively with stereotypes of competence (Cuddy, Fiske, & Glick, 2007;Fiske, 2010), and that there are descriptive and prescriptive stereotypes that link lower SES with academic incompetence among adults and children (Batruch, Autin, & Butera, 2017;Croizet & Claire, 1998;Goudeau & Croizet, 2016).…”
Section: Identity Incompatibilitymentioning
confidence: 99%
“…Research focusing on gender has shown the importance of identity compatibility in explaining gender inequalities in STEM subjects. Reflecting women’s historical underrepresentation in STEM fields and the masculine stereotypes associated with STEM (Eagly & Koenig, 2021), women tend to perceive lower levels of compatibility between their gender identity and the stereotypes about successful STEM students than men do. Lower levels of identity compatibility in STEM are associated with reduced belonging, confidence, motivation, and performance in STEM fields, and thus contribute to gender‐based inequalities in STEM outcomes (Ahlqvist, London, & Rosenthal, 2013; Good, Rattan, & Dweck, 2012; Rosenthal, London, Levy, & Lobel, 2011; Settles, 2004; Settles, Jellison, & Pratt‐Hyatt, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For a more general discussion on the nature and content of stereotypes, including how and why they develop, see literature on the stereotype content model (Fiske et al, 2002), social role theory (Koenig & Eagly, 2014), and the developmental intergroup theory of social stereotypes and prejudice (Bigler & Liben, 2006). Research on the pervasiveness and stability of stereotypes over time and cultures is also available (Charlesworth & Banaji, 2021;Diekman & Eagly, 2000;Eagly & Koenig, 2021;Eagly et al, 2020;Haines et al, 2016;Heilman & Eagly, 2008;Miller et al, 2015).…”
Section: Stereotypes and Perceived Incongruitymentioning
confidence: 99%
“…Communion is still firmly associated with women, and stereotypes of men appear more resistant to change than those of women [43][44][45]. In terms of role engagement, implicit tests showed that parenthood is more strongly associated with women than men [46], and only given role change, stereotype change can eventually be expected [47]. Even though a trend towards neutrality within gender stereotypes can be observed, it is estimated to take at least 134 years for implicit malecareer/female-family associations to dissolve [48].…”
Section: Masculinity Norms Fathering Norms and Parental Leavementioning
confidence: 99%